2017
DOI: 10.1080/00071668.2017.1311008
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the skeletal morphology of red jungle fowl

Abstract: 1. The skulls and postcranial skeletons of the red jungle fowl (Gallus gallus) were compared osteometrically between the populations from North and South Vietnam, North and Central Laos and Southeast Bangladesh. The populations include the three subspecies of G. g. spadiceus, G. g. gallus and G. g. murghi and were sampled to reveal the geographical morphological variations among populations in G. gallus. 2. The morphometric characteristics of subspecies murghi could be clearly distinguished from those of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Muscular weights were determined in the 68 male carcasses consisting of red jungle fowl, agricultural breeds (Sonia [Hy‐Line Sonia], Fayoumi, Rhode Island Red), and fighting breeds (Japanese Shamo [various Shamo] and Thai fighting cocks [Pra‐doo‐hang‐dam and Leang‐hang‐kaow]). The red jungle fowl samples used in this study were identified as G. gallus spadiceus based on locality and external appearance (Delacour, 1977 ; Endo et al, 2017 ; Johnsgard, 1999 ; Nishida et al, 2000 ). Fayoumi is a traditional laying breed, whereas Rhode Island Red is a popular dual‐purpose breed (Ekarius, 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Muscular weights were determined in the 68 male carcasses consisting of red jungle fowl, agricultural breeds (Sonia [Hy‐Line Sonia], Fayoumi, Rhode Island Red), and fighting breeds (Japanese Shamo [various Shamo] and Thai fighting cocks [Pra‐doo‐hang‐dam and Leang‐hang‐kaow]). The red jungle fowl samples used in this study were identified as G. gallus spadiceus based on locality and external appearance (Delacour, 1977 ; Endo et al, 2017 ; Johnsgard, 1999 ; Nishida et al, 2000 ). Fayoumi is a traditional laying breed, whereas Rhode Island Red is a popular dual‐purpose breed (Ekarius, 2007 ).…”
Section: Methodsmentioning
confidence: 99%